Capacitor Device for Air Bubbles Monitoring - Abdalrahman , Mawahib Gafare; Adam, Abdallah Belal; Dennis , John Ojur; Steele, Gail Sylvia (IJENS Publishers, 2009)
Emboli or Air bubble detection is vital for many medical procedures involving Extracorporeal Blood Circuits or ECBC e.g. hemodialysis, hemofiltration and cardiopulmonary bypass .This risk has increased as negative pressures are developed between the arterial fistula needle and the blood pump in the ECBC machine. This study suggests a capacitor device to detect the presence of air bubbles by measuring change in the output voltage. The capacitor has two platinum plates with area 0.75 cm2. The distance between the plates is 1 cm and Dextran70 fluid is introduced as the dielectric material between the plates. This solution replaces blood to avoid clotting whilst conducting the experiment. This device is connected with a resistor i.e. 100 kΩ to form a low pass filter circuit. The change of output voltage is measured when there is a change of dielectric material of the capacitor due to the appearance of an air bubble in the stream. The sensitivity of the capacitor device is found to be 8.28 mV/ nF at 2 MHz.